2006
DOI: 10.1177/107179190601200401
|View full text |Cite
|
Sign up to set email alerts
|

Bullying: From the Playground to the Boardroom

Abstract: Bullying in organizations has become one the prime social phenomena which can have a direct as well as indirect impact on the productivity of employees and managers. While bullying is a part of the fabric of society, the rate of occurrence as well as the severity of bullying acts in the workplace is alarming. This paper puts forth a model that illustrates the triangular relationship and interaction between the three components in the bullying event: 1) the organizational environment and its impact on the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 41 publications
2
92
0
Order By: Relevance
“…The second form of bullying identified by Harvey et al (2006), threats to personal standing by insulting or teasing the victim was also mentioned by several interviewees. An example with sending inappropriate emails or text messages, described by Interviewee 24 is related to this: "So a guy was fired for a text that was commenting on a girl or something like that.…”
Section: The Forms That Bullying Takes In the Ict Workplacementioning
confidence: 96%
See 4 more Smart Citations
“…The second form of bullying identified by Harvey et al (2006), threats to personal standing by insulting or teasing the victim was also mentioned by several interviewees. An example with sending inappropriate emails or text messages, described by Interviewee 24 is related to this: "So a guy was fired for a text that was commenting on a girl or something like that.…”
Section: The Forms That Bullying Takes In the Ict Workplacementioning
confidence: 96%
“…The definition provided here is a generic one so that it can encompass a range of bullying situations and contexts. For example, Harvey et al (2006) identified five groups of behaviours related to workplace bullying. These behaviours are related to isolation by preventing access to opportunities or withholding important information, threats to personal standing by insulting or teasing the victim overwork through an increase of workload to targeted individuals, as well as reminding the victim of their failures, and humiliating them in public which can damage their professional status.…”
Section: Workplace Bullyingmentioning
confidence: 99%
See 3 more Smart Citations